A multicomponent reaction of 2-aminoimidazoles: Microwave-assisted synthesis of novel 5-aza-7-deaza-adenines - Lim, F.; Low, S.; Ho, E.; Halcovitch, N.; Tiekink, E.; Dolzhenko, Anton (Royal Society of Chemistry, 2017)
An efficient and highly selective multicomponent synthesis of 4-aminoimidazo[1,2-a][1,3,5] triazines, which are 5-aza-7-deaza-isosteres of adenine, was developed. The reaction of 2-aminoimidazoles, triethyl orthoformate and cyanamide under microwave irradiation proceeded regioselectively to provide a library of novel 5-aza-7-deaza-adenines in good yields and purity. The developed method was demonstrated to be scalable and highly reproducible i n three different monomode microwave reactors. A rearrangement was proposed to explain the high selectivity of the reaction.